Land cover changes in the Air Telang Protected Forest, South Sumatra, Indonesia (1989-2013) (Biodiversitas Journal of Biological Diversity, 2017)
Eddy S, Iskandar I, Ridho MR, Mulyana A. 2017. Land cover changes in the Air Telang Protected Forest, South Sumatra, Indonesia (1989-2013). Biodiversitas 18: 1538-1545. The Air Telang Protected Forest (ATPF) is a mangrove forest in the Banyuasin District, South Sumatra, Indonesia. It has an area of about 12,660.87 ha. In fact, that the ATPF area has been converted into aquacultures, plantations, agricultural lands, settlements and ports during recent decades. The objective of this study is to identify the land cover changes in the ATPF from 1989 through 2013 using satellite remote sensing data. Three Landsat satellite imageries for 1989, 2001 and 2013 have been used to build maps and to predict the land cover changes in the study area. A ground-truthing verification was done to increase the accuracy of image classification in each region. The results showed that the anthropogenic forcing had caused significant degradation of primary mangrove forest in the ATPF from 1989 to 2013. This forcing was categorized as mangrove conversion into coconut plantations, oil palm plantations, aquacultures, farms, ports, and settlements. Of these six conversions, the coconut plantations, oil palm plantations and aquacultures have potential tendencies to increase construction that could threaten the existence of mangrove forest in ATPF. It was found that during 2013, the coconut plantations, oil palm plantations, and aquacultures accounted for about 18.0% (2,278.62 ha), 4.7% (591.87 ha) and 3.1% (386.18 ha) of mangrove forest changes, respectively.
Keywords: Air Telang Protected Forest; degradation; land cover changes; mangrove forest